2017
DOI: 10.3168/jds.2016-11837
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of milk infrared spectra for the retroactive application of calibration models

Abstract: The objective of this study was to standardize the infrared spectra obtained over time and across 2 milk laboratories of Canada to create a uniform historical database and allow (1) the retroactive application of calibration models for prediction of fine milk composition; and (2) the direct use of spectral information for the development of indicators of animal health and efficiency. Spectral variation across laboratories and over time was inspected by principal components analysis (PCA). Shifts in the PCA sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…The effectiveness of standardization for reducing prediction errors when transferring calibration models between instruments for fat composition traits has been demonstrated previously (Grelet et al, 2015;Bonfatti et al, 2017a). Grelet et al (2017) also demonstrated the effectiveness of standardization for reducing prediction errors for traits with lower quality calibration models such as methane emissions and cheese yield.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…The effectiveness of standardization for reducing prediction errors when transferring calibration models between instruments for fat composition traits has been demonstrated previously (Grelet et al, 2015;Bonfatti et al, 2017a). Grelet et al (2017) also demonstrated the effectiveness of standardization for reducing prediction errors for traits with lower quality calibration models such as methane emissions and cheese yield.…”
Section: Introductionmentioning
confidence: 87%
“…A third source of noise is the variation between instruments or within instruments across time. This variation, which exists even between instruments of the same brand, can result in prediction errors and bias and is particularly problematic when applying calibration models developed on one instrument across a historical database of spectra collected on different instruments (Grelet et al, 2015;Bonfatti et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the developed method is valid only once a slave instrument has been integrated in the network and has analyzed the standardization samples. Recently, a study aimed to standardize spectra over instruments and over time using historical data sets as a basis (Bonfatti et al, 2017a). This method allows the harmonizing of historical databases and the use a posteriori of models when instruments have not been standardized.…”
Section: Discussionmentioning
confidence: 99%